Hacking biofilm developed in a structured-bed reactor (SBRRIA) with integrated processes of nitrogen and organic matter removal - dos Santos, Carla Eloísa Diniz (2021)
Biomass samples from a structured-bed reactor subjected to recirculation and intermittent aeration (SBRRIA) were analyzed to investigate the bacterial community shift along with the changes in the C/N ratio. The C/N ratios tested were 7.6 ± 1.0 (LNC) and 2.9 ± 0.4 (HNC). The massive sequencing analyses revealed that the microbial community adjusted itself to different organic and nitrogenous applied loads, with no harm to reactor performance regarding COD and Total-N removal. Under LNC, conventional nitrification and heterotrophic denitrification steered the process, as indicated by the detection of microorganisms affiliated with Nitrosomonadaceae, Nitrospiraceae, and Rhodocyclaceae families. However, under HNC, the C/N ratio strongly affected the microbial community, resulting in the prevalence of members of Saprospiraceae, Chitinophagaceae, Xanthomonadaceae, Comamonadaceae, Bacillaceae, and Planctomycetaceae. These families include bacteria capable of using organic matter derived from cell lysis, ammonia-oxidizers under low DO, heterotrophic nitrifiers–aerobic denitrifiers, and non-isolated strains of Anammox. The DO profile confirmed that the stratification in aerobic, anoxic, and anaerobic zones enabled the establishment of different nitrogen degradation pathways, including the Anammox. Graphic abstract: [Figure not available: see fulltext.]